2020
DOI: 10.1016/j.csbj.2020.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Naught all zeros in sequence count data are the same

Abstract: Graphical abstract

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
110
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(113 citation statements)
references
References 84 publications
(116 reference statements)
3
110
0
Order By: Relevance
“…S15-S18). Our observation is consistent with another recent study [ 42 ], whose authors observed that “zero-inflated models lead to higher false-negative rates than identical non-zero-inflated models.” Hence, our real data analysis results are based on NB-GAM. However, realizing the complexity of biological systems and scRNA-seq protocols, we leave the choice between NB-GAM and ZINB-GAM as an option for users of PseudotimeDE, and we encourage users to plot their known DE genes as in Additional file 1 : Figs.…”
Section: Discussionsupporting
confidence: 93%
“…S15-S18). Our observation is consistent with another recent study [ 42 ], whose authors observed that “zero-inflated models lead to higher false-negative rates than identical non-zero-inflated models.” Hence, our real data analysis results are based on NB-GAM. However, realizing the complexity of biological systems and scRNA-seq protocols, we leave the choice between NB-GAM and ZINB-GAM as an option for users of PseudotimeDE, and we encourage users to plot their known DE genes as in Additional file 1 : Figs.…”
Section: Discussionsupporting
confidence: 93%
“…S15–S18). Our observation is consistent with another recent study [42], whose authors observed that “zero-inflated models lead to higher false-negative rates than identical non-zero-inflated models.” Hence, our real data analysis results are based on NB-GAM. However, realizing the complexity of biological systems and scRNA-seq protocols, we leave the choice between NB-GAM and ZINB-GAM as an option for users of PseudotimeDE, and we encourage users to plot their known DE genes as in Figs.…”
Section: Discussionsupporting
confidence: 93%
“…The zero inflation, or “dropout” issue, remains perplexing and controversial in the single-cell field [4042]. The controversy is regarding whether excess zeros that cannot be explained by Poisson or negative binomial distributions are biological meaningful or not.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, microbiome omic data are complex, as it is (i) compositional, e.g., provided as relative abundances, which require specific considerations when selecting statistical analyses ( Gloor et al, 2017 ), (ii) highly sparse, such that the interpretation of zero-values generated from sampling, biological, or technical processes heavily affects data-derived conclusions ( Silverman et al, 2020 ), and (iii) high dimensional, which increases modeling difficulty due to the influence of feature selection that heavily affect potential predictions ( Bolón-Canedo et al, 2016 ). Furthermore, multi-omic studies may contain gaps within the omic spectrum, such that certain samples may not be represented within a certain omic layer ( Lloyd-Price et al, 2019 ).…”
Section: Analysis Of Community Characteristics and Dynamicsmentioning
confidence: 99%